The Co-Occurrence of Overweight and Micronutrient Deficiencies or Anemia among Women of Reproductive Age in Malawi. Issue 6 (9th April 2020) - Rhodes, Elizabeth C; Suchdev, Parminder S; Narayan, K M Venkat; Cunningham, Solveig; Weber, Mary Beth; Tripp, Katie; Mapango, Carine; Ramakrishnan, Usha; Hennink, Monique; Williams, Anne M
ABSTRACT: Background: In low-resource settings, urbanization may contribute to the individual-level double burden of malnutrition (DBM), whereby under- and overnutrition co-occur within the same individuals. Objective: We described DBM prevalence among Malawian women by urban-rural residence, examined whether urban residence was associated with DBM, and assessed whether DBM prevalence was greater than the prevalence expected by chance given population levels of under- and overnutrition, which would suggest DBM is a distinct phenomenon associated with specific factors. Methods: We analyzed nationally representative data of 723 nonpregnant women aged 15–49 y from the 2015–2016 Malawi Micronutrient Survey. DBM was defined as co-occurring overweight or obesity (OWOB) and ≥1 micronutrient deficiency or anemia. We used Poisson regression models to examine the association between urban residence and DBM and its components. The Rao-Scott modified chi-square test compared the observed and expected DBM prevalence. Results: Nationally, 10.8% (95% CI: 7.0, 14.5) of women had co-occurring OWOB and any micronutrient deficiency and 3.4% (95% CI: 1.3, 5.5) had co-occurring OWOB and anemia. The prevalence of co-occurring OWOB and any micronutrient deficiency was 2 times higher among urban women than rural women [urban 32.6 (24.1, 41.2) compared with rural 8.6 (5.2, 11.9), adjusted prevalence ratio: 2.0 (1.1, 3.5)]. Co-occurring OWOB and anemia prevalence did not significantly differ by residence [urban 6.9 (0.6, 13.2) compared with rural 3.0 (0.8, 5.3)]. There were no statistically significant differences in observed and expected prevalence estimates of DBM. Conclusions: This analysis shows that co-occurring OWOB and any micronutrient deficiency was higher among women in urban Malawi compared with rural areas. However, our finding that co-occurring OWOB and any micronutrient deficiency or anemia may be due to chance suggests that there may not be common causes driving DBM in Malawian women. Thus, there may not be a need to design and target interventions specifically for women with DBM.